Survey of the Performance of Operating Room Personnel Regarding the Observance of Surgical Safety Principles in Hospitals of Mazandaran University of Medical Sciences in 2019 - Omid Zadi Akhule; Mojgan Lotfi; Ebrahim Nasiri; Saba Chalangari; Yasna Torkali pur (Tehran University of Medical Sciences, 2021)
Background and Aim: In order to improve patient safety, countries are seeking to monitor the safety of health systems and since surgical safety is an important part of patient safety, this study aimed to determine performance of Operating Room Personnel regarding the observance of surgical safety principles. Materials and Methods: This cross-sectional descriptive study was conducted on operating rooms of hospitals of Mazandaran university of medical sciences in 2019. Research population included 271 personnel of operating room selected via stratified random sampling. Data were collected using demographic characteristics questionnaire and Surgical Safety Checklist of the World Health Organization. The data was analyzed using SPSS software. Results: The mean scores of performance of surgical technologists in the circulating and scrub roles and anesthesia technologists regarding the observance of surgical safety principles, were 23.2±3.1, 18.4±3 and 28.2±3.5 respectively. The performance level of all three specialties was moderate. Findings showed that there was a significant difference between performance score with educational level. The mean score of performance was significantly higher in the technologists with bachelor's degree as compared to the technologists with associate degree (p<0.05). Conclusion: Considering that the performance of the participants of the study regarding the observance of surgical safety principles, it was not at a desirable level, thus it is recommended to encourage operating room personnel to upgrade their education and to continue monitoring the performance of them regarding the observance of surgical safety principles.